Effects of Bio-Green Fertilizers on Growth and Yield of Tomato in Net House Condition - Nan, Phetra; Touch, Visalsok; Horn, Linan; Serey, Mardy (AgriMalS, 2025)
Tomato (Solanum lycopersicum L.) is a widely cultivated crop that is particularly suitable for net house farming due to its high susceptibility to various biotic and abiotic stressors such as diseases, pests, and climate change. This study was conducted to investigate the effects of different levels of bio-green fertilizer on the growth and yield of tomato plants under net house conditions, with the aim of identifying the optimal fertilizer level that produces the highest yield. The experiment was carried out in Thmor Kre Kandal Village, Thmor Kre Commune, Chit Borey District, Kratie Province, over a period of four months and 24 days, from December 14, 2022, to May 10, 2023. Three tomato varieties - Phearum F1, Platinum F1, and Paetai - were used in the study. The experimental design followed a Randomized Complete Block Design (RCBD) with three replications and nine treatment combinations, resulting in a total of 27 subplots. The following growth and yield parameters were measured: stem height, number of branches, number of good fruits, number of damaged fruits, weight of good fruits, weight of damaged fruits, total number of fruits, and total fruit weight. Data collection was performed nine times at 10-day intervals throughout the experimental period. Based on the data analysis, it can be concluded that the interaction between fertilizer levels and tomato varieties significantly influenced plant growth and yield performance. Among the treatment combinations, the interactions involving the Platinum tomato variety T6 (S2F3) and T8 (S3F2) produced the highest total fruit yield and total fruit weight. In particular, treatment T8 (S3F2) - which combined a moderate level of bio-green fertilizer with balanced NPK application - showed the best overall results in terms of good fruit weight, total number of fruits, and total fruit weight. Therefore, this treatment is considered most suitable for net house cultivation and may serve as a model for future greenhouse and net house tomato production systems.